AN ANALYSIS OF DIRECTIVE ILLOCUTIONARY ACTS PERFOMED IN “ROMEO AND JULIET” MOVIE: PRAGMATICS APPROACH - Fadil Juliano; Rohit La Ami; Arman Syahadan; Afriana Afriana (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
. It is impossible to rule out the execution of the directive action while waiting for the interlocutor to perform an act. The speaker must take directive action in order to persuade the interlocutor to do something. This study is concerned with the implementation of directive speech acts and seeks to identify the various types and forms of directive speech acts. The goal of this research was to help readers understand the discussion of linguistics, particularly directive acts. In practice, this research should assist speakers in carrying out their intentions through directive actions. Thus, by comprehending the directive speech act, the interlocutor should be able to grasp the speaker's intention. The purpose of this research was to analyze the types and forms of directive acts in Romeo and Juliet movie. It was a qualitative research. The theory applied in determining the types of directive acts by Searle & Vanderveken (1985). The method used in data collection was the observation method. From the results of observations found 20 directive act utterances. The results of the research conducted on the collected data, found five types of directive acts, namely asking, ordering, forbidding, permitting, and praying. Of all these types, the type of directive that appeared the most was asking because the characters in the movie Romeo and Juliet conveyed a lot of utterances that demanded the interlocutor to provide information. On the other hand, the data showed that the type that appeared the least was praying because there were only a few prayer scene in the movie and the characters rarely pray outside that scene. The forms of directive act were interrogative, imperative, declarative.